Influence of organizational capabilities and environmental factors on internationalization strategy of SMEs - Ahmed, I. K.; Raja Yusof, Raja Nerina; Abdul, Mohani; D., Nadarajah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The study discusses organizational capabilities in relation to entrepreneurial experience, innovation, networking and external environmental factors consisting of industry and market, international network relationship, international innovativeness and international market skill to explain internationalization of SMEs. The paper draws on theoretical push and pull framework to explain the constructs and present the intermediating factor between push and pull forces and internationalization of SMEs. The review of literature shows that international entrepreneurial orientation and export promotion program as intermediating variables in the model can increase or lessen the interactive forces of pull and push factors. The study discussed evidence of relationship between the research constructs and how the interactive forces influence the internationalization of SMEs.